Flatness and Alignment Analysis of Conformity Measuring Instrument Design in X-Ray Modality - Hermawan, Aska Putri; Pudji, Andjar; Mak’ruf, Muhammad Ridha (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
A surface's verticality or horizontalness can be determined as well as its flatness using a waterpass or spirit level. The alignment and flatness of the X-ray tube and bucky table, which determine the perpendicularity of the X-ray beam, is one of the factors for the Conformance Test, according to PERKA BAPETEN No. 2 of 2018. A traditional waterpass is typically used to obtain that conclusion, but the measurement outcome is still subject to human error because there is no set value. To aim for exact alignment, A digital waterpass using the MPU6050 sensor is made, which produces precise X-Ray images, reduces noise in the form of shadow magnification, and investigates the function of the waterpass in the compliance of the X-Ray unit. Arduino is used as the data processor in this investigation. The output is then shown on an LCD and transmitted over Bluetooth to a computer where it is displayed using Delphi before being saved in Excel. With the deviation standard value of 10 degrees, we have obtained an error value from this research between 2% and 3%, minimum, which is 0.04 for sensor 1 and 0.25 for sensor 2. Sensors 1 and 2 measure 14 degrees at 0.089 and 0.054, respectively. The MPU6050 sensor can be utilized in this study to determine how flat the X-Ray tube and bucky table are about one another. This study's contribution is anticipated to be more effective tool testing, and the data will be kept on file until the next testing session.